Issues of Exploitation of Sharks by Thai Commercial Fisheries in the Andaman Sea - Sirachai Arunrugstichai (Prince of Songkla University, 2023)
Thesis (M.Sc., Ecology (International Program))--Prince of Songkla University, 2018